2016
DOI: 10.1016/j.meegid.2016.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Coccidian parasites of fish encompass profound phylogenetic diversity and gave rise to each of the major parasitic groups in terrestrial vertebrates

Abstract: Fish are the oldest and most diverse group of vertebrates; it therefore stands to reason that fish may have been the original hosts for many types of extant vertebrate parasites. Here, we sought to determine whether coccidian parasites of fish are especially diverse. We therefore sampled such parasites from thirty-nine species of fish and tested phylogenetic hypotheses concerning their relationships, using 18S rDNA. We found compelling phylogenetic support for distinctions among at least four lineages of pisci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…Recent phylo genetic works (Molnár et al 2012, Rosenthal et al 2016) have validated deep evolutionary distinctions among the coccidian parasites of fish, including (but not limited to) a monophyletic assemblage restricted to true members of the genus Eimeria. Subdivisions within Goussia correspond to morphological and developmental attributes that likely warrant further taxonomic revision.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent phylo genetic works (Molnár et al 2012, Rosenthal et al 2016) have validated deep evolutionary distinctions among the coccidian parasites of fish, including (but not limited to) a monophyletic assemblage restricted to true members of the genus Eimeria. Subdivisions within Goussia correspond to morphological and developmental attributes that likely warrant further taxonomic revision.…”
Section: Discussionmentioning
confidence: 99%
“…Among Goussia spp. collected from Hungarian fishes, Rosenthal et al (2016) found that molecular sequences of species with small dispersed oocysts developing in the gut of their hosts throughout the year differ from those of species with large oocysts developing seasonally in nodules and epicellular sites. Large differences were also found between nodular and epicellular species.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Goussia spp. are found in fish, reptiles and amphibians, which have not been extensively studied 812 at the cell biological level (Rosenthal et al, 2016). Overall, why the two different extant forms of 813 budding exist cannot be answered with satisfaction based on the factors we considered.…”
mentioning
confidence: 98%